Increasing Adolescents' Knowledge of Zero Waste Lifestyle in Pabuaran Village, Mt. Sindur - Krisnanda, Veno Dwi; Albab, Suhfi; Husna, Ainul; Arifin, Deasy Dwi Cahyaningtyas (Global Education Journal, 2023)
The Community Service Program (PKM) aims to socialize the Zero Waste (ZW) environmental program and train the public to manage waste (used goods) into usable items (recycled) using an e-mail-based application. The methods used are lectures and demonstrations (direct training), and counseling. For education on the Zero Waste environmental program, namely using the Zero Waste application that was developed previously, while for training on the utilization of waste into more useful goods, it is carried out through demonstrations or hands-on training (practice). This community service place is in Pabuaran Village, Mount Sindur, West Java. In this activity the researchers used the Participatory Action Research (PAR) method, which is a research method that is carried out in a participatory way among community members in a community. So far, no training has been held on waste management and the Zero Waste environment, so that people's knowledge and awareness about environmental health is still low. The results obtained are the formation of public knowledge about the importance of the Zero Waste environment and the community being able to make or manage waste into more useful finished goods.